Linfoma de Hodgkin Clássico: perfil de duas décadas de um serviço de referência em Fortaleza-Ceará - Mesquita, Juliene Lima (2020)
Classical Hodgkin's lymphoma (CHL), a type of cancer that originates in lymph nodes, arises when a lymphocyte turns into an uncontrolled malignant cell that affects the lymph node chains. The stage of CLH may vary from I to IV according to the extent of the disease. The ways of treating CHL depend on the stage of the disease, which may be through chemotherapy (CT), radiotherapy (RT) and / or hematopoietic stem cell transplantation (HSCT). The aim of the study was to describe the epidemiological and clinical characteristics of patients undergoing treatment with the ABVD protocol associating them with overall survival (OS) and event free survival (EFS). Descriptive and retrospective study of patients diagnosed with CHL seen at the Walter Cantídio University Hospital (HUWC) from 2000 to 2018 who underwent ABVD treatment. Patients were grouped in decades from 2000 to 2009 and from 2010 to 2018, and into patients with and without immunohistochemically examination. Chi-square test was performed to establish the association between mortality and relapse variables through univariate analysis. Subsequently a multivariate analysis of predictors through binary logistic regression. Survival was determined using the Kaplan-Meier Log-Rank test method. A total of 314 patients were included in the study group from 2000 to 2018. The age group with the highest incidence of the disease was the less and/or equal of 45 years 278 (88.54%), with a majority of males 159 (50.5%), NE histological subtype with 234 (74.52%), presence of B symptoms in 230 (73.25%), first-line treatment with 6 cycles of ABVD in 145 (45.8%), RT treatment was used in 133 (42.2%) and complete response in 197 (62.74). When distributed over decades, from 2000 to 2009 and 2010 to 2018, similarities were observed in the mean age of patients, with a predominance of the age group younger than 45 years, urban origin, stage II, presence of symptoms B, advanced stage and subtype nodular sclerosis. In the total patient group, bivariate analysis were predictive factors for mortality, age over 45 years (p = 0.0273), clinical staging IIIB and IVB (p = 0.0064), use of radiotherapy (p < 0.0011) and the complete answer (p = 0.0001) were significant. Multivariate analysis confirmed that the age greater than 45 years (p = 0.02) had a higher chance of death. While the complete response (p = 0.000) and the use of radiotherapy (p = 0.008) were protective factors for death. In the univariate analysis of relapse predictors, treatment without radiotherapy (p = 0.0080) and time longer than 1 year for diagnosis (p = 0.0040) had a higher chance of recurrence while complete response (p <0.0001) presented less association with relapse. In the multivariate, patients without response to therapy (p = 0.001), ABVD therapy without RT (p = 0.009) and time of diagnosis greater than 1 year (p = 0.012) had a higher chance of relapse. The variables that influenced OS were related to age below 45 years (p = 0.0252), use of RT (p = 0.0002), response to complete treatment (p <0.0001) and time less than 1 year of diagnosis (p <0.0001) had a higher OS. Regarding EFS, the time greater than 1 year after diagnosis (p = 0.0106) had a negative influence. The study showed a prevalence of males, aged 45 and under, with subtype NE, advanced stage, presence of symptoms B and presented complete response to ABVD. The factors that influenced the highest death were age over 45 years, treatment without the use of RT, non-response to therapy and diagnosis time greater than 1 year. The factors that influenced the highest recurrence were treatment without RT and the diagnosis time greater than 1 year. Predictors that influenced the decrease in OS were older than 45 years, treatment without RT, non-response to treatment and diagnosis time greater than 1 year.